2012
DOI: 10.1136/medethics-2011-100123
|View full text |Cite
|
Sign up to set email alerts
|

Ethical approval in developing countries is not optional

Abstract: When conducting health and medical research it is not only important to do the research ethically, but also to apply for prior ethical approval from the relevant authorities. The latter requirement is true for developed countries as well as developing countries. We argue that simply applying for research ethics approval from an institutional review board at a university based in a developed country is not enough to start a health research project in a developing country. The paper also suggests a number of rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 6 publications
0
10
0
1
Order By: Relevance
“…The research methods section is very detailed, describing the mixed-methods approach We have noted this missing link in other health studies conducted in Nepal [2,3]. It would be more informative for the researchers and wider communities to be provided with detailed information such as the tools used in this survey, whether the tools were developed in Nepali and if they were validated prior to conducting the survey.…”
Section: The Survey Methodsmentioning
confidence: 99%
“…The research methods section is very detailed, describing the mixed-methods approach We have noted this missing link in other health studies conducted in Nepal [2,3]. It would be more informative for the researchers and wider communities to be provided with detailed information such as the tools used in this survey, whether the tools were developed in Nepali and if they were validated prior to conducting the survey.…”
Section: The Survey Methodsmentioning
confidence: 99%
“…Identificar los aspectos del consentimiento informado relacionados con la metodología del protocolo de investigación es un deber del Comité de Ética de la Investigación (11,12). La interrelación entre el protocolo y el proceso de consentimiento es un asunto que el Comité debe examinar con el propósito de determinar si los criterios de inclusión interfieren con el proceso de reclutamiento de los sujetos, y si estos procesos de alguna forma coaccionan la decisión sobre la participación en el estudio.…”
Section: Deber Del Comité De éTicaunclassified
“…However, it is generally agreed that research collaborations between developed and developing countries should be ethically reviewed in both the host and the PI’s country of residence as standard practice ( Hyder et al, 2004 ), thus enabling the specificities of each context to be taken into account ( Ravinetto et al, 2011 ). One has to assume that the paucity of developing country RECs had a significant impact on the number of projects reviewed within the host countries, but there are a number of other possible reasons why researchers from developed countries may fail to apply for ethical approval in a developing country regardless of REC availability, including: ignorance, perceptions of cost, an assumption that certain research is exempt (as demonstrated above), arrogance or paternalism ( Van Teijlingen and Simkhada, 2012 ). As demonstrated by the quotes from Interviewees 3 and 4 above, at least some of the ESPA/ESRC-DFID award holders fall into one or more of these categories.…”
Section: Attitudes Towards Ethical Reviewmentioning
confidence: 99%